Training adult education practitioners: A collection of modules - Ellis, Patricia (CARCAE, 1988)
These five modules cover: 1) characteristics of adults, 2) adult learning, 3) motivation and participation, 4) designing teaching-learning activities, and 5) facilitating change. Each module has a rationale, specifies objectives, and provides exercises
Keywords: Adult educators